How information about the time requirements and legacy effects of treatments influence decision-making in patients with diabetes and hypertension - Laiteerapong, Neda (BMJ Open Diabetes Res Care, 2016)
OBJECTIVE: When deciding about diabetes treatments, patients are typically uninformed about how much time is required before (time requirements), or for how long treatments change outcomes (legacy effects). However, patients may be motivated to adopt treatments with time-related treatment information. We explored whether this information alters a patients' likelihood of starting medications. RESEARCH DESIGN AND METHODS: We conducted semistructured interviews with 60 adults with type 2 diabetes for <10 years and hypertension on oral medications. We measured change in likelihood of starting medications after receiving time requirement (diabetes, 10 years; hypertension, 3 years) and legacy effect (diabetes, 10 additional years; hypertension, none) information. Responses were analyzed for themes about time-related treatment information. RESULTS: At baseline, 70% of participants reported being very likely to start a recommended medication. Nearly half (40%) were less likely to start a diabetes medication after being informed of time requirements; but after being informed of legacy effects, 32% reported being more likely. Fewer participants changed likelihoods of starting antihypertensives with time-related information. Many participants expressed that medications' benefits were important to them regardless of time-related information. Participants considered time requirements for diabetes medications too long and compared them to their life expectancy. Many participants were interested in legacy effects of diabetes medications because they looked forward to discontinuing medications, although some expressed doubt that benefits could persist after stopping medications. CONCLUSIONS: While prolonged time requirements may dissuade patients from adopting treatments, the promise of legacy effects may motivate patients to commit to diabetes treatments.